Economic evaluation of HIV testing for men who have sex with men in community-based organizations – results from six European cities. Issue 8 (3rd August 2017) - Perelman, Julian; Rosado, Ricardo; Amri, Omar; Morel, Stéphane; Rojas Castro, Daniela; Chanos, Sophocles; Cigan, Bojan; Lobnik, Miha; Fuertes, Ricardo; Pichon, François; Kaye, Per Slaaen; Agustí, Cristina; et al.
ABSTRACT: The non-decreasing incidence of HIV among men who have sex with men (MSM) has motivated the emergence of Community Based Voluntary Counselling and Testing (CBVCT) services specifically addressed to MSM. The CBVCT services are characterized by facilitated access and linkage to care, a staff largely constituted by voluntary peers, and private not-for-profit structures outside the formal health system institutions. Encouraging results have been measured about their effectiveness, but these favourable results may have been obtained at high costs, questioning the opportunity to expand the experience. We performed an economic evaluation of HIV testing for MSM at CBVCT services, and compared them across six European cities. We collected retrospective data for six CBVCT services from six cities (Copenhagen, Paris, Lyon, Athens, Lisbon, and Ljubljana), for the year 2014, on the number of HIV tests and HIV reactive tests, and on all expenditures to perform the testing activities. The total costs of CBVCTs varied from 54, 390€ per year (Ljubljana) to 245, 803€ per year (Athens). The cost per HIV test varied from to 41€ (Athens) to 113€ (Ljubljana). The cost per HIV reactive test varied from 1966€ (Athens) to 9065€ (Ljubljana). Our results show that the benefits of CBVCT services are obtained at an acceptable cost, in comparison with the literature (values, mostly from the USA, range from 1600 to 16, 985 per HIV reactive test in clinical and non-clinical settings). This result was transversal to several European cities, highlighting that there is a common CBVCT model, the cost of which is comparable regardless of the epidemiological context and prices. The CBVCT services represent an effective and "worth it" experience, to be continued and expanded in future public health strategies towards HIV.